Interpreting the Early Modern World Transatlantic Perspectives - Beaudry, Mary C.; Symonds, James; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Although historical archaeologists often explore similar themes, the intellectual traditions in the United States and the United Kingdom lead to differing interpretations of these themes. The contributions to this innovative volume provide a bridge between a US-based archaeologist and a UK-based archaeologist on the themes of landscape studies, urban archaeology, memory and memorialization, gender studies, the lives of industrial workers, and archaeological biographies. The chapters are not meant to stand in isolation, but rather provide a dialog between both groups. This work explores the strengths of interpretive historical archaeology in the US and the UK, as well as compare and contrast differing approaches. It aims to foster debate and productive collaborations between historical archaeologists from different geographic regions. It will of interest to UK and US-based archaeologists, as well as those performing interpretive historical archaeology in other regions who will benefit from the insights it provides.
Part I. Country Estates/Landscapes: An American Landscape Conversation -- The Archaeology of Estate Landscapes in Eighteenth-Century England -- Part II. Archaeology of 19th century and the Lives of Working People: Section Introduction -- Urban Historical Archaeology: A View from the Golden Gate -- Celebrating Steel City: Historical Archaeology in Sheffield, U.K -- Part III. Conflict and Memorialization: Section Introduction -- "Remembering the Raid of 1704": Writing and Exhibiting Contested Histories in Historic Deerfield -- Monuments, Memory, and Resistance in the Scottish Highlands -- Part IV. Material Culture, Embodiment, Life Course, Identity: Section Introduction -- Stitching Women$1 (Bs Loves: Interpreting the Artifacts of Sewing and Needlework -- The Intimacy of Death: Expressions of Identity and Grief in Medieval and Renaissance Burial Rites -- Part V. Industrial Housing/Landscapes: Section Introduction -- "You Knew Where you Were": Practicing Class in (Post) Industrial Cheshire -- The Study of the Early Industrial Landscapes of the Swansea Region -- Part VI. Archaeological Biographies: Section Introduction -- The Large Writ Small: Landscape, Archaeography, and the Battle for Meaning -- Biographies of Long Life. Part VII. Commentary.s
Keywords: Social sciences; Atoms; Physics; Archaeology; Social Sciences; Archaeology; Atomic, Molecular, Optical and Plasma Physics; Electronic books